THE ROLE OF ACTORS IN THE POLICY NETWORK IN THE MINAPOLITAN AREA IN XIII KOTO KAMPAR - Ema Fitri Lubis,; Sujianto,; Febri Yuliani,; Auradian Marta, (Proceeding International Conference on Social Sciences, 2026)
Minapolitan is a concept of marine and fisheries-based economic development, grounded in the principles of integration, efficiency, quality, and acceleration. The Minapolitan area itself is part of a region that has a primary economic function consisting of production centres, processing, marketing of fishery commodities, services, and/or other supporting activities. The potential for fisheries business development in Kampar Regency is quite extensive and has considerable opportunities for development. The policy network in the context of Minapolitan also reflects collaboration between the government, local communities, and other stakeholders in the policymaking and implementation process. The purpose of this study is to explore and analyse the role of actors in the policy network in the Minapolitan area in XIII Koto Kampar. The approach used is qualitative. Informants include cross-sector stakeholders who play a role in the policy network of the Minapolitan area in XIII Koto Kampar. The results of the study indicate that the role of actors based on policy-making indicators has been effective, playing a part in formulating the direction, strategy, and regulations of the program. The coordinator indicator shows that there is integration between institutions/agencies and ensures the alignment of policy implementation. The facilitator indicator shows that there is a lack of training and assistance for the farming community. The implementer indicator shows that technical actors are available to run the Minapolitan program. Furthermore, the supporting indicators show that there are financial institutions, academics, and community groups that provide support for the implementation of this Minapolitan program, but the role of financial institutions in providing capital for fish farmers is not yet optimal. In the Minapolitan area, the development of efficient marketing channels is part of a broader policy network, which is a supporting indicator. The research findings show that synergy between actors in the policy network, in the form of coordination and communication, will strengthen the sustainability of the development of the Minapolitan area in XIII Koto Kampar.